Scaling up Index-based Flood Insurance (IBFI) for agricultural resilience and flood-proofing livelihoods in developing countries - Amarnath, Giriraj; Malik, Ravinder Paul Singh; Taron, Avinandan (International Water Management Institute, 2021)
This research report presents the first comprehensive framework of business models in terms of developing, marketing and scaling Index-based flood insurance (IBFI). The report evaluated ten case studies on agricultural insurance schemes (macro, meso and micro levels), globally, to develop public-private partnership business models for creating value (product development) and capturing value (product marketing). This report highlights four broad groups of interrelated factors that influence the uptake and scaling of agricultural insurance: (i) behavioral factors that influence farmers’ enthusiasm to invest in insurance; (ii) financial factors that stipulate governments’ willingness to provide financial support; (iii) legal and regulatory factors, which set ground rules for fair business and govern their adherence by stakeholders; and (iv) facilitating factors, including product design and development, business models, research and development, data availability, and awareness creation, which help ensure an efficient supply of insurance services. In summary, the report highlights the need for designing innovative IBFI and its potential benefits for uptake, and efforts for implementing IBFI as a potential risk transfer tool for comprehensive climate risk management among small-scale and marginal farmers.